Secagem de fatias de maçã pré-tratadas com ultrassom - Souza, Mariana Gonçalves (2018)
The objective of this work was to investigate the effect of immersion in water with or without the use of ultrasound as a method of increasing mass transfer before drying apple slices. Pretreatment was performed in an ultrasonic bath at 25 ° C. Ultrasonic power was supplied at 25 kHz frequency for 10, 25 and 40 min in the ultrasound bath. The treatments that did not receive the ultrasound waves were immersed in water at 25 ºC in times 10, 25 and 40 min. The drying process was performed after pre-treatments in a wind tunnel dryer with a fixed temperature of 70øC and an air velocity of 1.5 m / s. The effects of pre-treatment with ultrasound after drying were investigated. The empirical models of Henderson & Pabis modified and Page provided the best adjustments of the drying curves. It had its time reduced by up to 9% when pre-treatment with ultrasound occurred. Pre-treatments improved the parameters of apple quality, such as rehydration capacity, a very important parameter after drying.